Developing Criminal Procedure Law Policy in Accordance with Resolution No. 27-NQ/TW of the Vietnam Communist Party Central Committee - Truc, Huynh Trung (VNU Journal of Science: Legal Studies; Vol 41 No 2DO - 10.25073/2588-1167/vnuls.4661, 2025)
Resolution No. 27-NQ/TW dated November 9 th , 2022, of the 13 th Party Central Committee on continuing to build and perfect the Vietnamese socialist rule-of-law state in the new period affirms several key principles. These include ensuring the supremacy of the Constitution and law; the State’s governance based on the Constitution and law; the respect for, assurance of, and protection of human rights and citizens' rights; and placing the people at the center, as both the goal and driving force of national development. The Resolution also sets out new requirements for improving the legal system, strengthening law implementation mechanisms, and enhancing the quality of legal human resources. The article focuses on clarifying core orientations of criminal procedural law policy in the new period in the spirit of Resolution 27-NQ/TW.